Chemical Composition of a Novel Distillate from Fermented Mixture of Nine Anti-Inflammatory Herbs and Its UVB-Protective Efficacy in Mouse Dorsal Skin via Attenuating Collagen Disruption and Inflammation - Her, Young (Molecules, 2020)
Since ancient times, various herbs have been used in Asia, including Korea, China, and Japan, for wound healing and antiaging of the skin. In this study, we manufactured and chemically analyzed a novel distillate obtained from a fermented mixture of nine anti-inflammatory herbs (Angelica gigas, Lonicera japonica, Dictamnus dasycarpus Turcz., D. opposita Thunb., Ulmus davidiana var. japonica, Hordeum vulgare var. hexastichon Aschers., Xanthium strumarium L., Cnidium officinale, and Houttuynia cordata Thunb.). The fermentation of natural plants possesses beneficial effects in living systems. These activities are attributed to the chemical conversion of the parent plants to functional constituents which show more potent biological activities. In our current study, the distillate has been manufactured after fermenting the nine oriental medical plants with Lactobacillus fermentum, followed by distilling. We analyzed the chemical ingredients involved in the distillate and evaluated the effects of topical application of the distillate on ultraviolet B (UVB)-induced skin damage in Institute of Cancer Research (ICR) mice. Topical application of the distillate significantly ameliorated the macroscopic and microscopic morphology of the dorsal skin against photodamage induced by UVB radiation. Additionally, our current results showed that topical application of the distillate alleviated collagen disruption and reduced levels of proinflammatory cytokines (tumor necrosis factor alpha and interleukin 1 β expressions) in the dorsal skin against UVB radiation. Taken together, our current findings suggest that the distillate has a potential to be used as a material to develop a photoprotective adjuvant.